Cerebrospinal fluid neurofilament light chain levels in children with acquired demyelinating syndrome - Wu, Wenlin; Hou, Chi; Wu, Wenxiao; Shen, Huiling; Zeng, Yiru; Chen, Lianfeng; Liao, Yinting; Zhu, Haixia; Tian, Yang; Peng, Bingwei; Chen, Wen-Xiong; Li, Xiaojing (Frontiers in Pediatrics, 2024)
Objective To study the cerebrospinal fluid (CSF) neurofilament light chain (NfL) in pediatric acquired demyelinating syndrome (ADS) and its association with factors of laboratory and imaging results. Methods We analyzed clinical data from children with ADS collected from May 2020 to January 2021 at the Department of Neurology of Guangzhou Women and Children's Medical Center. Enzyme-linked immunosorbent assays were used to detect the CSF NfL of patients. Results Thirty pediatric ADS patients (17 male, 13 female) were included in the study. The most frequent diagnosis was uncategorized ADS (36.7%, 11/30), followed by acute disseminating encephalomyelitis (ADEM) (23.3%, 7/30), myelin oligodendrocyte glycoprotein antibody-associated disorder (MOGAD) (20.0%, 6/30), NMO (6.7%, 2/30), multiple sclerosis (MS) (6.7%, 2/30), and neuromyelitis optic spectrum disorders (NMOSD) (6.7%, 2/30). The median CSF NfL for the first time was 7,425.28 pg/ml (interquartile range, 1,273.51, >10,000 pg/ml). CSF NfL increase over normal value (<290.00 pg/ml for people younger than 30 years old) was seen in 98.7% of patients. Patients were divided into uncategorized ADS, ADEM, MOGAD, and MS/NMO/NMOSD groups, with no significant difference in CSF NfL between each group. The CSF NfL positively correlated with the immunoglobulin (Ig) G (ρ = 0.473) and IgE (ρ = 0.366). However, the CSF NfL did not correlate with CSF white blood count and CSF protein. Furthermore, there was no significant difference between patients with oligoclonal bands positive and without. The CSF NfL negatively correlated with interferon γ (ρ = −0.501), CD45 + CD3+ T (ρ = −0.466), CD45 + CD3 + CD4+ T (ρ = −0.466), and CD45 + CD3 + CD8+ T cells (ρ = −0.521). However, it did not correlate with CD45 + CD19+ B cells. CSF NfL in patients with cerebral white matter lesions in MRI was higher than in patients without. Moreover, the CSF NfL positively correlated with the number of brain MRI locations (ρ = 0.362). Nine patients underwent multiple detections of CSF NfL, and their CSF NfL for the last detection was not significantly different from the first. Conclusions The CSF NfL increases significantly in pediatric ADS, and it can be a biomarker of neuro-axonal injury and a good indication of the extent of lesions.